Development journalism and its potential contribution to the state building: the case of Somalia - Ahmed, Ismail Sheikh Yusuf (Penerbit Universiti Kebangsaan Malaysia, 2016)
Development aspect is a key target and agenda for all governments in the world. The concept embraces different facets of development including political, social, economic, infrastructure, societal, environmental, and intellectual aspects. Numerous factors contribute to the achievement of the above goals. Among these is a communication policy factor; an effective and comprehensive policy can help the state accelerate development success rate. In underdeveloped countries, the mass media play an essential role in mediating the development in the country. Systematic and comprehensive communication policies are greatly needed in these countries compared to developed and developing countries. In Somalia, where there was no effective and functioning state since 1990s, the need for such policies is great. The country has been in chaotic and unstable political situation, where the media has negatively contributed to hostility and conflict. In this paper, the author discusses the concept of development journalism and its evolution and relevance particularly to the newly independent states in Asia and Africa since 1960s. Although some people may argue that, the concept is out of date; this author believes that it is more relevant in today’s current political dilemma in Somalia. The paper provides numerous rationales for adopting the development journalism and how it can contribute to the state building efforts. Implications for policy and decision-makers were also discussed along these lines. For media practitioners, the paper recommends to follow peace journalism when covering tribal and political conflicts and to fully participate in current development projects.